Four-horned wasps, description of some remarkable Dirhinus (Hymenoptera, Chalcididae) from Kenya, with a discussion of their taxonomic placement - Delvare, Gérard; Copeland, Robert S. (Zootaxa, 2018)
Five new species belonging to Dirhinus Dalman are described: D. quadrhinus Delvare sp. nov., D. gigasetosus Delvare sp. nov., D. kambae Delvare sp. nov., D. maasaii Delvare sp. nov. and D. leakeyorum Delvare sp. nov. These species belong to the newly defined and characterized quadrhinus species group, included in the subgenus Dirhinus of Dirhinus Dalman. Evidence for this taxonomic placement is provided despite the distinctive morphology exhibited by the relevant species. The himalayanus, claviger, anthracia and hesperidum groups, also included in subgenus Dirhinus, are similarly defined and characterized and lists of the relevant described species are provided. A key to the females of the quadrhinus group is given. The phylogeny of the genus Dirhinus, especially the other subgenera Pareniaca and Hontalia is discussed as well as the morphological characters the genus Dirhinus in relation to the potential hosts, and the restricted distribution of the members of the quadrhinus group in Kenya.